Platinum-cobalt alloy / topological carbon defect composite material as well as preparation method and application thereof

By using platinum-cobalt alloy to support topological carbon defective materials in fuel cell catalysts, the problem of insufficient precious metal properties and stability of existing platinum-based catalytic materials is solved, and more efficient oxygen reduction reaction and reaction stability are achieved.

CN119400876APending Publication Date: 2025-02-07HAINAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411536198.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In existing proton exchange membrane fuel cells, the kinetic inert of oxygen reduction reaction (ORR) leads to an increase in overpotential and a decrease in cell efficiency, and the precious metallicity and stability of platinum-based catalytic materials are insufficient, limiting their large-scale application.

Method used

The zeolite imidazole ester skeleton material was prepared by co-precipitation and standing method, and carbonized at high temperature and annealed under a nitrogen protection atmosphere to form a carbon material rich in topological carbon defects. Then, a platinum-cobalt alloy was introduced under a reducing atmosphere to prepare a platinum-cobalt alloy/ Topological carbon defect composites.

Benefits of technology

This composite material significantly improves the intrinsic activity and reaction stability of the catalyst by reducing the amount of platinum used and provides more active sites through topological carbon defects, and improves the electrochemical performance of the oxygen reduction reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400876A_ABST
    Figure CN119400876A_ABST
Patent Text Reader

Abstract

The invention provides a platinum-cobalt alloy / topological carbon defect composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) preparing a zeolite imidazate framework material through a coprecipitation standing method; (2) performing high-temperature carbonization on the zeolite imidazate framework material to obtain a nitrogen-rich carbon material; (3) removing nitrogen from the nitrogen-rich carbon material at a high temperature in a nitrogen protection atmosphere to obtain a carbon material rich in topological carbon defects; and (4) introducing the platinum-cobalt alloy through alloying in a reducing atmosphere to obtain the platinum-cobalt alloy / topological carbon defect composite material. According to the prepared platinum-cobalt alloy / topological carbon defect composite material, the usage amount of Pt is reduced, and meanwhile the electrochemical performance and the reaction stability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular to a platinum-cobalt alloy / topological carbon defect composite material, and a preparation method and application thereof. Background Art

[0002] my country's energy structure has long been dominated by fossil energy. The excessive use of fossil fuels has led to serious environmental problems and has also posed severe challenges to my country's energy security. Therefore, the development of clean energy is urgent. Hydrogen energy has the advantages of high calorific value and zero pollution, and is an important part of the future energy system. Therefore, hydrogen energy conversion technology will become one of the important research directions in the future energy field. Fuel cells are important devices for hydrogen energy applications, and their industrial development will directly promote the application of hydrogen energy technology. Among them, proton exchange membrane fuel cells have attracted widespread attention due to their high energy conversion rate, low-temperature start-up, and green environmental protection. The anode of the proton exchange membrane fuel cell undergoes a hydrogen oxidation reaction (HOR), and the cathode undergoes an oxygen reduction reaction (ORR). The inertia of HOR and ORR in reaction kinetics will lead to an increase in the overpotential of the fuel cell and a decrease in battery efficiency.

[0003] Compared with HOR, ORR involves the adsorption of O2 and the breaking of O=O bonds, where the bond enthalpy of the O=O bond in the O2 molecule is as high as 494 kJ mol -1 , the breaking of this bond has greater kinetic inertness and higher energy requirements, which greatly restricts the efficiency of fuel cell energy conversion. At present, commercial fuel cells mainly use platinum-based catalytic materials. This is because according to Sabatier's law, the activity of ORR catalytic materials is directly related to their adsorption and desorption properties of oxygen-containing intermediates. Too weak adsorption is not conducive to the occurrence of the reaction, and too strong adsorption will hinder the reaction. Compared with other metal catalysts, metal platinum catalytic materials are at the top of the active volcano diagram. This excellent adsorption and desorption performance makes it one of the most ideal ORR catalytic materials. However, platinum is a precious metal. It is expensive and scarce in reserves, and it cannot be applied on a large scale. In addition, under acidic working conditions, metal platinum will dissolve, migrate, agglomerate, etc., resulting in insufficient stability. Therefore, it is urgent to rationally design platinum-based catalytic materials to reduce the amount of Pt used while improving the intrinsic activity and reaction stability of the catalyst. Summary of the invention

[0004] Based on this, the object of the present invention is to provide a platinum-cobalt alloy / topological carbon defect composite material, a preparation method and application thereof.

[0005] In a first aspect, the present invention provides a method for preparing a platinum-cobalt alloy / topological carbon defect composite material, comprising the following steps:

[0006] (1) preparing zeolite imidazolate framework material by coprecipitation static method;

[0007] (2) carbonizing the zeolite imidazolate framework material at high temperature to obtain a nitrogen-rich carbon material;

[0008] (3) removing nitrogen from the nitrogen-rich carbon material at high temperature under a nitrogen protective atmosphere to obtain a carbon material rich in topological carbon defects;

[0009] (4) In a reducing atmosphere, platinum-cobalt alloy is introduced by alloying to obtain a platinum-cobalt alloy / topological carbon defect composite material.

[0010] Compared with the prior art, the present invention loads the platinum-cobalt alloy on the carbon defect material, reducing the amount of Pt used. At the same time, by high-temperature annealing the zeolite imidazolate framework material under a nitrogen protection atmosphere, a carbon material rich in five-element topological defects is obtained, and a large number of active sites are constructed to anchor the alloy nanoparticles, so that the platinum-cobalt alloy / topological carbon defect composite material has excellent electrochemical properties and reaction stability.

[0011] In one embodiment, in step (3), a carbon material rich in pentagonal topological carbon defects is obtained.

[0012] In one embodiment, in step (1), the particle size of the zeolite imidazolate framework material is 200-1000 nm.

[0013] In one embodiment, step (1) comprises the following steps:

[0014] The methanol solution containing 2-methylimidazole and the methanol solution containing zinc nitrate are mixed, stirred vigorously, and allowed to stand for aging to obtain a precipitate;

[0015] The precipitate is washed and dried to obtain a zeolite imidazolate framework material.

[0016] In one embodiment, 4 g zinc nitrate and 5 g 2-methylimidazole were dissolved in 500 mL methanol solution respectively.

[0017] In one embodiment, in step (4), the reducing atmosphere is argon hydrogen gas.

[0018] In one embodiment, step (4) comprises the following steps:

[0019] The carbon material rich in topological carbon defects is placed in a mortar, a platinum precursor, a cobalt precursor and deionized water are added and fully ground, and the ground mixed powder is heat-treated in an argon-hydrogen reduction atmosphere to obtain a platinum-cobalt alloy / topological carbon defect composite material.

[0020] In a second aspect, the present invention provides a platinum-cobalt alloy / topological carbon defect composite material prepared by the preparation method described above.

[0021] In a third aspect, the present invention provides an application of the platinum-cobalt alloy / topological carbon defect composite material as described above in an oxidation-electroreduction catalytic reaction.

[0022] In a fourth aspect, the present invention provides an oxygen electrochemical reduction catalyst, comprising the platinum-cobalt alloy / topological carbon defect composite material as described above. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 XRD diagrams of PtCo-DPC of Example 1 of the present invention and PtCo-NPC of Comparative Example 1;

[0025] FIG2( a) is a HR-TEM image of PtCo-DPC of Example 1 of the present invention;

[0026] FIG2( b ) is a HR-TEM image of PtCo-NPC of Comparative Example 1 of the present invention;

[0027] Figure 3 It is a comparison chart of LSV performance of Examples 1-3 of the present invention and Comparative Examples 1-2;

[0028] Figure 4 The electron paramagnetic resonance images of the DPC of Example 1 of the present invention and the NPC of Comparative Example 1;

[0029] Figure 5 The Raman spectra of the DPC of Example 1 of the present invention and the NPC of Comparative Example 1;

[0030] Figure 6 C1s XPS graphs of DPC of Example 1 of the present invention and NPC of Comparative Example 1;

[0031] Figure 7 C1s XPS graphs of PtCo-DPC of Example 1 of the present invention and PtCo-NPC of Comparative Example 1;

[0032] Figure 8 N1s XPS graphs of PtCo-DPC of Example 1 of the present invention and PtCo-NPC of Comparative Example 1;

[0033] FIG9( a) is a comparison diagram of the stability of PtCo-DPC before and after the reaction of Example 1 of the present invention;

[0034] FIG9( b ) is a comparison diagram of the stability of PtCo-DPC-C1 before and after the reaction of Example 2 of the present invention;

[0035] FIG9( c ) is a comparison diagram of the stability of PtCo-DPC-C2 before and after the reaction of Example 3 of the present invention;

[0036] FIG9( d ) is a comparison diagram of the stability of PtCo-NPC before and after the reaction of Comparative Example 1 of the present invention;

[0037] FIG9( e ) is a comparison diagram of the stability of Pt / C before and after the reaction of Comparative Example 2 of the present invention;

[0038] Fig.10 It is a comparison diagram of half-wave potential and mass activity of Examples 1-3 of the present invention and Comparative Examples 1-2;

[0039] Fig.11 4fXPS graphs of PtCo-DPC of Example 1 of the present invention and PtCo-NPC of Comparative Example 1;

[0040] Fig.12 Co 2p XPS graphs of PtCo-DPC of Example 1 of the present invention and PtCo-NPC of Comparative Example 1;

[0041] FIG13( a) is a CV curve diagram of PtCo-DPC of Example 1 of the present invention;

[0042] FIG13( b ) is a double-layer capacitance diagram of PtCo-DPC of Example 1 of the present invention;

[0043] FIG13( c ) is a CV curve diagram of PtCo-NPC of Comparative Example 1 of the present invention;

[0044] FIG13( d ) is a double-layer capacitance diagram of PtCo-NPC of Comparative Example 1 of the present invention;

[0045] FIG13( e) is a CV curve diagram of Pt / C of Comparative Example 2 of the present invention;

[0046] FIG13( f ) is a graph of the double-layer capacitance of Pt / C according to Example 2 of the present invention;

[0047] FIG14( a) is a TEM image of PtCo-DPC of Example 1 of the present invention;

[0048] FIG14( b) is a SEM image of PtCo-DPC-C1 of Example 2 of the present invention;

[0049] Figure 14(c) is a SEM image of PtCo-DPC-C2 of Example 3 of the present invention.

[0050] Among them, PtCo-DPC represents the platinum-cobalt alloy / topological carbon defect composite material of Example 1, DPC represents the carbon material rich in topological carbon defects of Example 1, PtCo-DPC-C1 represents the platinum-cobalt alloy / topological carbon defect composite material of Example 2, PtCo-DPC-C2 represents the platinum-cobalt alloy / topological carbon defect composite material of Example 3, PtCo-NPC represents the platinum-cobalt alloy / topological carbon defect composite material of Comparative Example 1, NPC represents the nitrogen-rich carbon material of Comparative Example 1, and Pt / C represents the commercial platinum-carbon catalyst of Comparative Example 2. DETAILED DESCRIPTION

[0051] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0052] The present invention provides a method for preparing a platinum-cobalt alloy / topological carbon defect composite material, comprising the following steps:

[0053] (1) preparing zeolite imidazolate framework material by coprecipitation static method;

[0054] (2) carbonizing the zeolite imidazolate framework material at high temperature to obtain a nitrogen-rich carbon material;

[0055] (3) carbonizing the nitrogen-rich carbon material at high temperature under a nitrogen protective atmosphere to obtain a carbon material rich in topological carbon defects;

[0056] (4) In a reducing atmosphere, a platinum-cobalt alloy is introduced by alloying to obtain a platinum-cobalt alloy / topological carbon defect composite material.

[0057] Wherein, step (1) comprises the following steps: mixing a methanol solution containing 2-methylimidazole and a methanol solution containing zinc nitrate, stirring vigorously, and then standing for aging to obtain a precipitate; washing and drying the precipitate to obtain a zeolite imidazolate framework material. Specifically, the zeolite imidazolate framework material is ZIF-8.

[0058] Optionally, in step (1), the amount of 2-methylimidazole is 4-6g, preferably 5g. Zinc nitrate is zinc nitrate hexahydrate, and the amount is 3-5g, preferably 4g. The amount of methanol is 400-600mL, preferably 500mL. Let stand and age at room temperature, the aging time is 12-24h, preferably 18h. The particle size of the zeolite imidazole ester framework material is 200-800nm, preferably 500nm.

[0059] Optionally, in step (2), the heating rate of high temperature carbonization is 1-10°C min -1 , preferably 5℃min -1The temperature after heating is in the range of 800-1000° C., preferably 900° C. The heat preservation time is 1-3 hours, preferably 2 hours.

[0060] Optionally, in step (3), the heating rate of high temperature carbonization is 1-10°C min -1 , preferably 5℃ min -1 The temperature after heating is 600-1000° C., preferably 800° C. The heat preservation time is 1-3 hours, preferably 2 hours.

[0061] Step (4) comprises the following steps: placing the carbon material rich in topological carbon defects in a mortar, adding a platinum precursor, a cobalt precursor and deionized water for thorough grinding, and heat treating the ground mixed powder in an argon-hydrogen reduction atmosphere to obtain a platinum-cobalt alloy / topological carbon defect composite material.

[0062] Optionally, in step (4), the platinum precursor is H2PtCl6·6H2O, and the cobalt precursor is Co(NO3)2·6H2O. The mass of H2PtCl6·6H2O is 5-10 mg, preferably 8 mg. The mass of Co(NO3)2·6H2O is 5-10 mg, preferably 8 mg. The mass of the carbon material rich in topological carbon defects is 50-100 mg, preferably 80 mg. The ground mixed powder is heated to a certain temperature A at a certain heating rate in a hydrogen and argon atmosphere, and then kept warm for a certain time B, and then naturally cooled to a certain temperature C and kept warm for a certain time D. Among them, the heating rate is 1-10℃ min -1 , preferably 5℃ min -1 ; Temperature A is 800-1000°C, preferably 900°C; insulation time B is 30-60min, preferably 45min; temperature C is 300-500°C, preferably 400°C; insulation time D is 2-4h, preferably 3h.

[0063] In the present invention, unless otherwise specified, the experimental methods used are all conventional methods, and the materials, reagents, etc. used can be purchased from commercial channels.

[0064] Specific embodiments are listed below to illustrate the present invention.

[0065] Example 1

[0066] In this embodiment, the preparation method of the platinum-cobalt alloy / topological carbon defect composite material includes the following steps:

[0067] (1) Preparation of zeolite imidazolate framework material

[0068] 4 g of zinc nitrate hexahydrate and 5 g of 2-methylimidazole were dissolved in a beaker containing 500 mL of methanol solution, respectively. The mixture was vigorously stirred at room temperature for 2 min until the solid was completely dissolved, and then sealed with plastic wrap. The mixture was then allowed to stand and aged for 18 h. The precipitate was washed 4 times with methanol solution and collected, and then dried in a vacuum oven at 60 ° C for 8 h to obtain a zeolite imidazole ester framework material.

[0069] (2) Preparation of nitrogen-rich carbon materials

[0070] 80 mg of zeolite imidazolate framework material was placed in the middle of a quartz tube and heated at 5 °C min -1 The heating rate was increased to 900℃ for annealing for 2h. After cooling naturally, the obtained black powder was treated with 8mol L -1 The product was washed with HCl solution and then dried in an oven for 8 h to obtain a nitrogen-rich carbon material.

[0071] (3) Preparation of carbon materials rich in topological carbon defects

[0072] The nitrogen-rich carbon material was placed in the middle of the quartz tube and heated at 5 °C min -1 The heating rate was increased to 800°C and annealed for 2 hours to obtain a carbon material rich in topological carbon defects (hereinafter referred to as "DPC").

[0073] (4) Preparation of platinum-cobalt alloy / topological carbon defect composites

[0074] 80 mg of carbon material rich in topological carbon defects was placed in a mortar, 8 mg of H2PtCl6·6H2O and 8 mg of Co(NO3)2·6H2O were added, and deionized water was added and fully ground. The ground mixed powder was placed in the middle of a quartz tube and heated at 5 °C min under an argon-hydrogen reducing atmosphere. -1 The heating rate was increased to 400°C and annealing was carried out for 3 hours to obtain a platinum-cobalt alloy / topological carbon defect composite material (hereinafter referred to as "PtCo-DPC").

[0075] Example 2

[0076] This embodiment provides a preparation method of a platinum-cobalt alloy / topological carbon defect composite material (hereinafter referred to as "PtCo-DPC-C1"), which differs from Example 1 only in the amount ratio of 2-methylimidazole, zinc nitrate and methanol in step (1), and 4.5g of zinc nitrate hexahydrate and 3g of 2-methylimidazole are dissolved in a beaker containing 500mL of methanol solution. The other preparation methods are the same as those in Example 1.

[0077] Example 3

[0078] This embodiment provides a preparation method of a platinum-cobalt alloy / topological carbon defect composite material (hereinafter referred to as "PtCo-DPC-C2"), which differs from Example 1 only in the amount ratio of 2-methylimidazole, zinc nitrate and methanol in step (1), and 3.5 g of zinc nitrate hexahydrate and 8 g of 2-methylimidazole are dissolved in a beaker containing 500 mL of methanol solution. The other preparation methods are the same as those in Example 1.

[0079] Comparative Example 1

[0080] In this comparative example, the preparation method of the platinum-cobalt alloy / nitrogen-doped carbon composite material comprises the following steps:

[0081] (1) Preparation of zeolite imidazolate framework material

[0082] 4 g of zinc nitrate hexahydrate and 5 g of 2-methylimidazole were dissolved in a beaker containing 500 mL of methanol solution, respectively. The mixture was vigorously stirred at room temperature for 2 min until the solid was completely dissolved, and then sealed with plastic wrap. The mixture was then allowed to stand and aged for 18 h. The precipitate was washed 4 times with methanol solution and collected, and then dried in a vacuum oven at 60 ° C for 8 h to obtain a zeolite imidazole ester framework material.

[0083] (2) Preparation of nitrogen-rich carbon materials

[0084] 80 mg of zeolite imidazolate framework material was placed in the middle of a quartz tube and heated at 5 °C min -1 The heating rate was increased to 900℃ for annealing for 2h. After cooling naturally, the obtained black powder was treated with 8mol L -1 The mixture was washed with HCl solution and then dried in an oven for 8 h to obtain nitrogen-rich carbon material (hereinafter referred to as "NPC").

[0085] (3) Preparation of platinum-cobalt alloy / topological carbon defect composites

[0086] 80 mg of nitrogen-rich carbon material was placed in a mortar, 8 mg of H2PtCl6·6H2O and 8 mg of Co(NO3)2·6H2O were added, and deionized water was added and fully ground. The ground mixed powder was placed in the middle of a quartz tube and spun at 5 °C min under an argon-hydrogen reducing atmosphere. -1 The heating rate was increased to 400°C and annealing was performed for 3 hours to obtain a platinum-cobalt alloy / nitrogen-doped carbon composite material (hereinafter referred to as "PtCo-NPC").

[0087] Comparative Example 2

[0088] In this comparative example, a standard Shanghai Hesen 20% commercial platinum-carbon catalyst (hereinafter referred to as "Pt / C") was purchased.

[0089] Test Example 1

[0090] The PtCo-DPC of Example 1 and the PtCo-NPC of Comparative Example 1 were subjected to X-ray diffraction analysis and HR-TEM imaging, and the results were as follows: Figure 1 and Figure 2. Figure 1 It can be seen that the PtCo-DPC of Example 1 contains three strong diffraction peaks, the (100) plane at 24.2° represents the peak of carbon, the (111) peak at 40.8° and the (200) plane at 47.1° represent the characteristic peaks of platinum-cobalt alloy; the PtCo-NPC of Comparative Example 1 also contains three strong diffraction peaks, the (100) plane at 25.8° represents the peak of carbon, the (111) peak at 40.2° and the (200) plane at 46.7° represent the characteristic peaks of platinum-cobalt alloy. Compared with the PDF standard card, it can be seen that both Example 1 and Comparative Example 1 synthesized a composite material of carbon-loaded platinum-cobalt alloy.

[0091] Compared with Comparative Example 1, the (111) peak position of Example 1 shifted 1.5 degrees, indicating that the introduction of the two alloy materials caused the material to produce shrinkage strain. Figure 2(a) , 2(b) The HR-TEM image shown shows that the interplanar spacing of the PtCo(111) surface in Example 1 is The interplanar spacing of the PtCo(111) surface in Comparative Example 1 is This is similar to Figure 1 The X-ray diffraction analysis results are consistent with those of the previous study. The lattice contraction effect of the PtCo alloy can weaken the platinum-oxygen binding energy, thereby promoting the kinetics of the oxygen reduction reaction.

[0092] Test Example 2

[0093] In an acidic electrolyte (0.1M HClO4), saturated mercury / mercurous sulfate (Hg / Hg2SO4) was used as a reference electrode, a carbon counter electrode, and the materials of Examples 1-3 and Comparative Examples 1-2 were used as working electrodes. First, under oxygen saturation conditions, the voltage was set at 100 mVs -1 CV cyclic activation was performed at a scan rate of 5 mV s -1 ) to test the electrochemical performance. The test results are as follows Figure 3As shown, the starting potential of PtCo-DPC in Example 1 can reach 0.97V, and the half-wave potential can reach 0.845V. The starting potential of PtCo-DPC-C1 in Example 2 is 0.82V, and the half-wave potential is 0.73V. The starting potential of PtCo-DPC-C2 in Example 3 is 0.85V, and the half-wave potential is 0.75V. In Comparative Example 1, the starting potential of PtCo-NPC is 0.78V, and the half-wave potential is 0.68V. In Comparative Example 2, the starting potential of Pt / C is 0.91V, and the half-wave potential is 0.821V.

[0094] It can be seen that compared with the PtCo-NPC of Comparative Example 1, the platinum-cobalt alloy / topological carbon defect composite materials of Examples 1-3 of the present invention have higher starting potentials and half-wave positions, and have better electrochemical properties. This is mainly because the platinum-cobalt alloy / topological carbon defect composite materials of Examples 1-3 of the present invention have rich five-element topological carbon defects. In topological carbon defects, carbon atoms carry unpaired electrons, which weaken the conjugated C=C bonds, resulting in unsaturated coordination of carbon atoms, and these unpaired electrons are very sensitive to external magnetic fields. Therefore, for completely graphitized carbon, there are no unpaired electrons due to the delocalization of the π* orbital. For carbon materials with fewer topological carbon defects, few unpaired electrons are formed and are not sensitive to external magnetic fields. For materials rich in topological carbon defects, a large number of unpaired electrons of carbon atoms are very sensitive to external magnetic fields, and a higher intensity of π* resonance intensity will be shown in the EPR results.

[0095] In order to study the defect type, the present invention obtains the Figure 4 The EPR diagram shown. Figure 4 It can be seen that the spectrum of DPC in Example 1 shows a clear symmetrical peak in the magnetic field value range of 3503 to 3522 mT, indicating that there are abundant pentagonal topological defects in DPC, while the NPC in Comparative Example 1 does not have an obvious symmetrical peak.

[0096] Furthermore, the present invention conducted high-precision Raman spectroscopy analysis on the DPC in Example 1 and the NPC in Comparative Example 1, and obtained Figure 5 .from Figure 5 It can be seen that the D / G band intensity ratio of DPC in Example 1 is 1.05, and the D / G band intensity ratio of NPC in Comparative Example 1 is 0.95, indicating that there are higher defects in DPC in Example 1, and the defect content of NPC in Comparative Example 1 is lower. In addition, the D3 fitting peak area represents the five-membered topological carbon defect. The D3 / G area ratio of DPC in Example 1 is 0.78, indicating that the five-membered topological defect content in DPC is dominant; the D3 / G fitting peak area ratio of NPC in Comparative Example 1 is 0.40, which is much lower than 0.78 of DPC in Example 1, indicating that the five-membered topological defect content in NPC is very small.

[0097] The present invention also analyzes the C1s XPS fitting spectra of the DPC in Example 1 and the NPC in Comparative Example 1, as shown in FIG. Figure 6 As shown. Among them, sp 3 C and sp 2 The ratio of C can be used to evaluate the degree of defects in carbon materials. Figure 6 It can be seen that the sp of DPC in Example 1 3 C / sp 2 C is 2.32, and the sp of NPC of comparative example 1 3 C / sp 2 C is 2.24. Therefore, the DPC of Example 1 of the present invention has abundant quinary topological defects, while the NPC of Comparative Example 1 has fewer quinary topological defects.

[0098] At the same time, the present invention also analyzes the C1s XPS fitting spectra of PtCo-DPC of Example 1 and PtCo-NPC of Comparative Example 1, as shown in FIG. Figure 7 As shown. Among them, the sp of PtCo-DPC in Example 1 3 C / sp 2 C is 1.02, much higher than 0.78 of PtCo-NPC in Comparative Example 1. Figure 8 The XPSN 1s fitting spectrum shown was analyzed, and the Pyrrole-N (Pr-N) content in the PtCo-NPC of comparative example 1 was 44.7%, and the Pyridine-N (Py-N) content was 30.6%, which was much higher than the 15.2% Pr-N content and 15.1% Py-N content in the PtCo-DPC of Example 1. It can be seen that the nitrogen species removal process of Pr-N and Py-N occurred during high-temperature annealing in the PtCo-DPC of Example 1, which is the key to the directional construction of five-membered topological carbon defects, and the degree of defects increased while the nitrogen content decreased.

[0099] Test Example 3

[0100] A 0.1 M HClO4 solution was used as the electrolyte, and a carbon counter electrode, such as the material of Example 1-3 and Comparative Example 1-2, was used as the working electrode. The oxygen solubility in the electrolyte was maintained at 100 mV s -1 CV cycles were performed at a scan rate of 5 mV s -1 The LSV test was performed at a scan rate of . The test results are shown in Figure 9(a)-9(e)As shown, the half-wave potential of PtCo-DPC in Example 1 was 0.845V in the first cycle. After 10,000 cycles, the half-wave potential of PtCo-DPC was 0.843V, with almost no attenuation. After 30,000 cycles, the half-wave potential was 0.822V. After 40,000 cycles, the half-wave potential could still reach 0.8V. After 10,000 CV cycles, the half-wave potential of PtCo-DPC-C1 in Example 2 decayed to 0.68V. After 10,000 CV cycles, the half-wave potential of Example 3 decayed to 0.66V. After 5,000 CV cycles, the half-wave potential of PtCo-NPC in Comparative Example 1 decayed to 0.63V. After 10,000 CV cycles, the half-wave potential of Comparative Example 2 decayed to 0.765V. For further reference Fig.10 It can be seen that the mass specific activity of PtCo-DPC in Example 1 is 1013.5 mA mg -1 pt , Example 2 is 267.3mA mg -1 pt , Example 3 is 311.6mA mg -1 pt , which is much higher than the mass specific activity of PtCo-NPC in Comparative Example 1 (61.8 mA mg -1 pt , and the mass specific activity of comparative example 2 is 49.3mA mg -1 pt Therefore, the PtCo-DPC of the present invention has a high activity in the oxygen reduction reaction in an acidic environment.

[0101] right Fig.11 The XPS Pt4f spectra and Fig.12 The Co 2p XPS spectrum shown in the figure is fitted and analyzed to show that the Pt 4f 7 / 2 and Pt 4f 5 / 2 Peak position, Co 2p 1 / 2 The peak positions all shifted negatively. Figure 13(a)-13(f) It can be seen that the double-layer capacitance of PtCo-DPC in Example 1 is 67.1 mFcm -2 , much higher than 4mF cm in Comparative Example 2 -2 The double layer capacitance is 42.1 mF cm-1, which is comparable to the comparative example 1PtCo-NPC. -2The double layer capacitance is close. When the electrochemical active area is similar, the performance of PtCo-DPC in Example 1 is significantly better than that of PtCo-NPC in Comparative Example 1. The element contents of PtCo-DPC in Example 1 and PtCo-NPC in Comparative Example 1 were precisely determined by ICP-OES. The results are shown in Table 1. The mass fractions of Pt and Co in PtCo-DPC in Example 1 are 2.37% and 1.70%, respectively, and the mass fractions of Pt and Co in PtCo-NPC in Comparative Example 1 are 1.33% and 1.15%, respectively.

[0102] Table 1 ICP-OES element contents of Example 1 and Comparative Example 1

[0103]

[0104] It can be seen from this that the PtCo-DPC of the present invention changes the direction of electron flow and regulates the electronic structure of the alloy elements due to the presence of the quinary topological defect, thereby being able to provide reaction active sites in an acidic environment, and can anchor the PtCo alloy with higher internal reaction activity, effectively limiting its migration and dissolution during the reaction process, and synergistically achieving an efficient oxygen reduction reaction.

[0105] Further referring to Figures 9 and 10, it can be seen that the electrochemical performance and stability of PtCo-DPC of Example 1 are better than those of Examples 2 and 3. The applicant has found through research that this is mainly related to the particle size of the zeolite imidazole ester framework material. The dosage ratios of dimethyl imidazole, zinc nitrate and methanol are different in Examples 1-3, and the particle sizes of the synthesized zeolite imidazole ester framework materials are different. As shown in Figure 14 (a)-(c), the particle size of PtCo-DPC in Example 1 is 500nm, the particle size of PtCo-DPC in Example 2 is 1000nm, and the particle size of PtCo-DPC in Example 3 is 200nm. When the particle size is small, the topological defect content of the zeolite imidazole ester framework material structure is limited, so that the number of anchored platinum cobalt alloy nanoparticles is also limited, and the anchoring ability is reduced, resulting in a decrease in the electrochemical activity and cyclic stability of PtCo-DPC. When the particle size is too large, the specific surface area of ​​the zeolite imidazole ester framework material is significantly reduced, which directly affects the electrochemical performance of PtCo-DPC. The particle size of the zeolite imidazolate framework material in Example 1 of the present invention is 500 nm, which can ensure the content of topological carbon defects in the subsequently synthesized composite material and the ability of topological carbon defects to anchor PtCo alloy nanoparticles, and can take into account the specific surface area of ​​the material, thereby ensuring the electrochemical performance and stability of PtCo-DPC.

[0106] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0107] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a platinum-cobalt alloy / topological carbon defect composite material, characterized in that: The following steps are involved: (1) preparing zeolite imidazolate framework material by coprecipitation static method; (2) carbonizing the zeolite imidazolate framework material at high temperature to obtain a nitrogen-rich carbon material; (3) removing nitrogen from the nitrogen-rich carbon material at high temperature under a nitrogen protective atmosphere to obtain a carbon material rich in topological carbon defects; (4) In a reducing atmosphere, a platinum-cobalt alloy is introduced by alloying to obtain a platinum-cobalt alloy / topological carbon defect composite material.

2. The method for preparing the platinum-cobalt alloy / topological carbon defect composite material according to claim 1, characterized in that: In step (3), a carbon material rich in pentagonal topological carbon defects is obtained.

3. The method for preparing the platinum-cobalt alloy / topological carbon defect composite material according to claim 1, characterized in that: In step (1), the particle size of the zeolite imidazolate framework material is 200-1000 nm.

4. The method for preparing the platinum-cobalt alloy / topological carbon defect composite material according to any one of claims 1 to 3, characterized in that: Step (1) comprises the following steps: The methanol solution containing 2-methylimidazole and the methanol solution containing zinc nitrate are mixed, stirred vigorously, and allowed to stand for aging to obtain a precipitate; The precipitate is washed and dried to obtain a zeolite imidazolate framework material.

5. The method for preparing the platinum-cobalt alloy / topological carbon defect composite material according to claim 4, characterized in that: Dissolve 4 g of zinc nitrate and 5 g of 2-methylimidazole in 500 mL of methanol solution respectively.

6. The method for preparing the platinum-cobalt alloy / topological carbon defect composite material according to any one of claims 1 to 3, characterized in that: In step (4), the reducing atmosphere is argon-hydrogen gas.

7. According to the method for preparing the platinum-cobalt alloy / topological carbon defect composite material according to any one of claims 1 to 3, step (4) comprises the following steps: The carbon material rich in topological carbon defects is placed in a mortar, a platinum precursor, a cobalt precursor and deionized water are added and fully ground, and the ground mixed powder is heat-treated in an argon-hydrogen reduction atmosphere to obtain a platinum-cobalt alloy / topological carbon defect composite material.

8. A platinum-cobalt alloy / topological carbon defect composite material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the platinum-cobalt alloy / topological carbon defect composite material as claimed in claim 8 in oxidation electro-reduction catalytic reaction.

10. An oxygen electrochemical reduction catalyst, characterized in that: Including the platinum-cobalt alloy / topological carbon defect composite material as described in claim 8.

Citation Information

Patent Citations

  • Preparation method and application of carbon material rich in topological defects obtained through high-temperature ammonia treatment

    CN112830468A

  • Carbon material / platinum composite material rich in topological defects and preparation method and application of carbon material / platinum composite material

    CN113066994A

  • Platinum-based alloy catalyst as well as preparation method and application thereof

    CN115842139A

  • Composite soft magnetic powdery material and magnetically biasing permanent magnetic core containing same

    US20090191421A1